Psychology of relationships - Vincy Joseph; Thomas,Smitha Biju; Hans,Basil V (Ghaziabad Pen and Paper Academy, 2025)
This book, The Psychology of Relationships: Attachment Theory and its Impact on Adult Relationships, is an exploration of how attachment theory illuminates the complexities of adult relationships. It seeks to bridge the gap between academic research and practical application, offering readers not just a theoretical framework but also tools for self-awareness and growth.
Keywords: Attachment Theory and its Impact on Adult Relationships; Psychology